Inflammatory bowel disease and primary immunodeficiency disorders: Clinical presentations and diagnostic work-up - Schwerd, T; Uhlig, H (Springer, 2017)
Background Inflammatory bowel disease (IBD) is a polygenic disorder with two major subtypes Crohn’s disease and ulcerative colitis. Genetic defects that cause primary immunodeficiencies or intestinal ephithelial barrier defects are increasingly recognized as monogenic causes of IBD. Objectives This leading article provides an overview about monogenic IBD, clinical presentations of patients and a diagnostic algorithm for suspected monogenic IBD. Materials and methods Review of literature regarding functional immunology tests and genetic diagnostics of monogenic IBD. Results More than 60 genes are associated with monogenic IBD and a spectrum of clinical presentations. These disorders are enriched in patients with early onset IBD occurring before the age of six years. Validated functional diagnostic tests are available for some PID disorders, e.g. chronic granulomatous disease, defects in IL-10 signaling, XIAP deficiency, defects in regulatory T cells or disorders of the CVID-SCID spectrum. Application of parallel sequencing by gene panel sequencing, exome or genome sequencing increases the diagnostic yield. Successful identification of a Mendelian type gene defect in IBD offers personalized therapies (e.g. curative stem cell transplantation or pathway-specific biologicals), allows family counseling and screening for infectious complications or malignancies, and helps to avoid unnecessary surgery including colectomy. Conclusions A rational diagnostic algorithm helps to diagnose monogenic IBD and offers individualized therapeutic strategies.